2014
DOI: 10.3390/molecules191117202
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Mediated Cytotoxic Effect of Copper(II) Hydrazone Complexes against Human Glioma Cells

Abstract: 2-Acetylpyridine acetylhydrazone (H2AcMe), 2-benzoylpyridine acetylhydrazone (H2BzMe) and complexes [Cu(H2AcMe)Cl2] (1) and [Cu(H2BzMe)Cl2] (2) were assayed for their cytotoxicity against wild type p53 U87 and mutant p53 T98 glioma cells, and against MRC-5 fibroblast cells. Compounds 1 and 2 proved to be more active than the corresponding hydrazones against U87, but not against T98 cells. Compound 1 induced higher levels of ROS than H2AcMe in both glioma cell lines. H2AcMe and 1 induced lower levels of ROS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Concentration dependent cytotoxicity was observed in mouse fibroblasts cells treated with Cu (Cao et al, 2012). In addition, ROS mediated cytotoxic effect were seen in exposure of Cu against human glioma cells (Recio Despaigne et al, 2014). The above evidence suggest and support that Cu can induce apoptosis in catfish, which was observed in the in vitro analysis, revealing morphological features characteristic of apoptosis.…”
Section: Discussionsupporting
confidence: 64%
“…Concentration dependent cytotoxicity was observed in mouse fibroblasts cells treated with Cu (Cao et al, 2012). In addition, ROS mediated cytotoxic effect were seen in exposure of Cu against human glioma cells (Recio Despaigne et al, 2014). The above evidence suggest and support that Cu can induce apoptosis in catfish, which was observed in the in vitro analysis, revealing morphological features characteristic of apoptosis.…”
Section: Discussionsupporting
confidence: 64%
“…20 This proposes that the cytotoxicity of Cu(SBCM) 2 could be due to the production of intracellular ROS as copper complex of other variants have found that they induced cell death by induction of high oxidative stress. [21][22][23][24][25] Unexpectedly, based on the DCFH-DA assay results (Fig. 8), Cu(SBCM) 2 did not increase the ROS production in both MCF-7 and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 82%
“…2-Benzoylpyridine-derived hydrazones present cytotoxic activity against several tumor cell lines. 1 3 In previous works, we demonstrated that upon coordination of these hydrazones to bismuth(III) 3 and gallium(III), 4 the cytotoxic effects against leukemia and solid tumor cells were improved in comparison to the free ligands.…”
Section: Introductionmentioning
confidence: 94%